2019
DOI: 10.24252/idaarah.v3i2.10264
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Iklim Kerja Terhadap Kinerja Guru Pada Madrasah Aliyah Di Kecamatan Gantarang Kabupaten Bulukumba

Abstract: This study aims to: 1) find out the description of the work climate at Madrasah Aliyah in Gantarang District, Bulukumba Regency; 2) find out the reality of teachers' performance at Madrasah Aliyah in Gantarang District, Bulukumba Regency; 3) determine the effect of the work climate on teachers' performance at Madrasah Aliyah in Gantarang District, Bulukumba Regency. This type of research is an ex post facto research as part of quantitative research. Respondents in this study were 75 teachers taken as a whole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…This study agrees with Hamsah et al (2019), who found that the work environment has a beneficial impact on teacher performance. The findings of De Roche's research (in Malang, 2012) confirm that the work climate may be split into two categories: negative and positive.…”
Section: Resultssupporting
confidence: 93%
“…This study agrees with Hamsah et al (2019), who found that the work environment has a beneficial impact on teacher performance. The findings of De Roche's research (in Malang, 2012) confirm that the work climate may be split into two categories: negative and positive.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, in his dissertation, examined the relationship between the working environment and teacher commitment in elementary schools in Alabama found a connection between a good school environment and more teachers' commitment. Nevertheless, in their research, Hamsah, Syamsuddhuha, & Rahman (2019) concluded that the work atmosphere affected teachers' performance at Madrasah Aliyah in Gantarang District. A conducive work atmosphere made the madrasah environment comfortable so that it would be one of the encouragements for teachers to conduct their duties properly.…”
Section: Resultsmentioning
confidence: 97%
“…This of course affects the work commitment of the teachers. One of the factors that measure the success of education in schools is the performance of teachers, because the teacher is one of the implementers of education that is indispensable (Hamsah et al, 2019). Teacher performance is a determining factor for student success in achieving achievement.…”
Section: Findings and Discussionmentioning
confidence: 99%